2013
DOI: 10.1016/j.annepidem.2013.07.022
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of sport-related traumatic brain injury and risk factors of severity: a population-based epidemiologic study

Abstract: Purpose Few studies of sport-related traumatic brain injury (TBI) are population-based or rely on directly observed data on cause, demographic characteristics, and severity. This study addresses the epidemiology of sport-related TBI in a large population. Methods Data on all South Carolina hospital and emergency department encounters for TBI, 1998–2011, were analyzed. Annual incidence rate of sport-related TBI was calculated, and rates were compared across demographic groups. Sport-related TBI severity was m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
73
2
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(83 citation statements)
references
References 50 publications
(54 reference statements)
4
73
2
4
Order By: Relevance
“…A previous population-based study found ∼61% of SRRCs occur in youth 0 to 18 years. 4 There are numerous studies demonstrating that many children and adolescents do not report concussion symptoms to any health care providers, but it is unclear how many people who experience symptoms have a true concussion diagnosis. 17,22,23,25,35,36 We applied rates from studies of middle and high school students underreporting concussions across younger age groups because there is little information on SRRC reporting in younger children.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A previous population-based study found ∼61% of SRRCs occur in youth 0 to 18 years. 4 There are numerous studies demonstrating that many children and adolescents do not report concussion symptoms to any health care providers, but it is unclear how many people who experience symptoms have a true concussion diagnosis. 17,22,23,25,35,36 We applied rates from studies of middle and high school students underreporting concussions across younger age groups because there is little information on SRRC reporting in younger children.…”
Section: Discussionmentioning
confidence: 99%
“…Our method of determining SRRCs was more inclusive than many previous studies, which excluded specific causes or required sports-and recreationrelated E-codes for inclusion. 4,11,12 Because MarketScan is dependent on International Classification of Disease, Ninth Revision, Clinical Modification (ICD-9-CM) codes and the presence of E-codes for injuries is variable, we used an exclusion method for classification of SRRCs in MarketScan. Sports and recreation, motor vehicle collisions, and falls account for ∼80% of concussions in children.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have described the incidence of sports-related TBI in adult ED populations. 10,23,46 Similarly, a large study in the Pediatric Emergency Care Applied Research Network, conducted between 2004 and 2006, recently reported that the overall incidence of sports-related TBI was 1%, with significant variation by type of sports. 20 However, the characteristics of inpatient hospital LOS, complications, discharge, and mortality rates in a large, nationally representative cohort have yet to be described.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported on the incidence of sports-related TBI in various ED populations. 10,17,39 However, the absence of inpatient and acute outcome data has precluded an analysis of hospital LOS, discharge disposition, and mortality rates after sports-related TBI. In the present analysis of an NTDB data set collected over a 10-year interval, we characterized the demographic profiles, hospital and ICU LOSs, medical complications, mortality rates, and discharge disposition across multiple broad categories of sports disciplines in adults admitted for sports-related TBI to Level I and Level II US trauma centers.…”
Section: Discussionmentioning
confidence: 99%